De moribus persecutorum - Gradel, Ittai (Religionsvidenskabeligt Tidsskrift, 1993)
Om baggrunden for de romerske kristenforfølgelser General remarks are presented on the subject of traditional Roman cults, and it is e.g. argued that the term "religion" is christianizing, and therefore usually leads to misunderstanding when applied to these cults, most clearly so in the field of emperor worship. This is symptomatic of the numerous methodological pitfalls involved in studying this phenomenon n particular and pagan Roman mentality in general. The conflict of the Roman state with Christianity is then dealt with and interpreted in the light of such traditionalist values as pietas and religio; it is argued that the all-decisive factors in Roman hostility towards Christians were not only the sect's exclusiveness but simply its novelty, which was in itself an abhorrence to traditionalist Roman mentality. On the basis of this interpretation, the edict of the emperor Decius demanding sacrifices to the gods appears difficult to explain in terms of traditional pagan piety; instead the edict is believed to have been aimed at Christianity from the very beginning.